THE EQUATION OF A STRAIGHT LINE AND A PARABOLA FORMED AS A RESULT OF A SYMMETRIC TRANSLATION WITH RESPECT TO A STRAIGHT LINE y=kx+b. - Mamatboyeva, Dilraboxon; Mamajonova, Feruza; Qo‘shaqova, Dilnoza; Muhammadjonova, Muslima (Educational Research in Universal Sciences, 2023)
Everyone knows mathematics is the science that deals with the logic of shape, quantity and arrangement. Math is all around us, in everything we do. It is the building block for everything in our daily lives, including mobile devices, computers, software, architecture (ancient and modern), art, money, engineering and even sports. In this paper, we study making symmetric shapes of any straight lines and parabolas. To do this, we use moving the origin of coordinate system and rotating it. And important thing is that we can find formulas for determining symmetric shapes of the given straight lines and giperbolas since we know coefficients of equations of the given straight lines and giperbolas.